Intervensi Pada Penderita Hordeolum - Adinda Husna Cahyana; Arfa Salma Firnandya; Muhammad Ammar Naufal; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
The eye is one of the body's senses that is sensitive to many things and easily gets an infection. Patients with infection or inflammation of the eyelids are often the first to present to the primary care physician. One of the conditions of infection of the eyelids is a stye or hordeolum. Hordeolum is the most common acute bacterial infection by Staphylococcus aureus that occurs on the eyelids. Hordeolum divided into two categories, internal and external. The sebaceous glands of the eyelash follicles (Glands of Zeiss) and the apocrine glands of Moll, both located on the margins of the lids, are the source of the external hordeolum. Meanwhile, the Meibomian glands, which are found on the inside of the eyelids, are the source of internal hordeolum. Although it occurs quite often, hordeolum does not have a definite incidence. All ages are affected, especially adolescents and young adults, and the onset is spontaneous or associated with risk factors such as eyelid hygiene and long-term disease. Diagnosis can be determined from clinical examination alone, while supporting examinations are carried out if there is suspicion of involvement of other parts of the eye that significantly interferes with the physical condition. Management is generally conservative in the form of warm compresses and cleaning the lids. Antibiotics are used if the condition is severe.